Raising the standard: Assessing the effectiveness of debate activities for English fluency in Indonesian police academy classrooms - Gatot Hadi Waluyo; Urip Sulistiyo; Mukhlash Abrar; Bunga Ayu Wulandari (EduLite: Journal of English Education, Literature and Culture, 2026)
This study examines how British Parliamentary Debate (BPD) is used to enhance English-speaking proficiency among third-year cadets at the Indonesian Police Academy (IPA). Grounded in an interpretivist perspective, it used a qualitative, single-site case study design to explore cadets’ and lecturers’ experiences with debate-based learning in police classrooms context. Data were collected through classroom observations, semi-structured interviews, focus group discussions, and document analysis using purposive sampling (34 cadets and 2 English lecturers). The data were analyzed thematically with NVivo 15 and guided by Miles and Huberman’s interactive analysis model, comprising data reduction, data display, and conclusion drawing/verification. The analysis highlights 5 interrelated thematic experiences in speaking improvement: initial involvement, emotional response, preparation process, topic relevance, and activity perception. Overall, debate-based learning offers a holistic approach to developing linguistic, cognitive, and affective skills and can be integrated more systematically into police-academy English curricula, particularly when reinforced through regular practice, collaborative peer work, and constructive feedback from lecturers.